Insecta, Hymenoptera, Bethylidae: range extension and filling gaps in Central African Republic - Celso Azevedo; Rayani Garcia; Fernanda Gobbi; Simon van Noort (Check List, 2015)
Bethylidae are cosmopolitan wasps, with about 100 valid genera and about 2,600 valid species around the world. This study aimed to determine the genera of Bethylidae occurring in Central African Republic. The specimens were collected at three sites using three collecting methods. A total of 1,924 specimens were obtained and 18 genera recorded: Apenesia, Cephalonomia, Dissomphalus, Epyris, Goniozus, Holepyris, Laelius, Pararhabdepyris, Parascleroderma, Plastanoxus, Pristocera, Protisobrachium, Pseudisobrachium, Sulcomesitius, Trachepyris, Trichiscus, Tuberepyris and Zimankos. All of these genera are recorded for the first time from this country.